A nickel cobaltate nanoparticle-decorated hierarchical porous N-doped carbon nanofiber film as a binder-free self-supported cathode for nonaqueous Li–O2 batteries. Issue 23 (25th May 2016) - Xue, Hairong; Mu, Xiaowei; Tang, Jing; Fan, Xiaoli; Gong, Hao; Wang, Tao; He, Jianping; Yamauchi, Yusuke
Abstract : Rechargeable nonaqueous lithium–oxygen (Li–O2 ) batteries have been considered a promising power source candidate due to their high theoretical energy densities. Abstract : Rechargeable nonaqueous lithium–oxygen (Li–O2 ) batteries have been considered a promising power source candidate due to their high theoretical energy densities. Here, we in situ fabricated a three-dimensional (3D) hierarchical porous hybrid film composed of NiCo2 O4 nanoparticle (NP)-decorated mesoporous N-doped carbon nanofibers (NCO@NCF), using single-nozzle co-electrospinning combined with annealing treatment. This hybrid film can serve directly as a binder-free self-supported cathode for Li–O2 batteries that exhibit high specific capacity (5304 mA h g −1 ), excellent rate capability, and outstanding cycling stability (close to 100 cycles), benefiting from its structural and material superiority. Its hierarchical porous structure not only can facilitate O2 diffusion and enhance electrolyte infiltration but also promises abundant Li2 O2 storage. In addition, crisscross N-doped carbon nanofibers with high graphitization form a perfect conductive network, which ensures the fast transmission of electrons and avoids binder-induced adverse side reactions. Moreover, the homogenously distributed NiCo2 O4 NPs possess efficient contact with both Li + and O2 and supply numerous catalytically active sites, thus leading to high-efficiency difunctional catalytic activities for the ORR and OER. Therefore, these encouraging results suggest an effective approach to obtaining high-performance nonaqueous Li–O2 batteries by optimizing the electrode structures and catalyst properties.